Creating a Learning Process and Adapting Technology to Improve Highland Rice Production, Wiang Haeng District, Chiang Mai Province, Thailand - Meepanya , Sumalee; Anuchyta , Jaruvee; Punyatuy , Sippawit; Hantanapong, Apiwat; Jaikawin , Suttakarn; Kanghae , Pitchanan (Area Based Development Research Journal, 2024)
This study was conducted in the mountainous regions of Ban Huai Krai (Piang Luang sub-district), Ban Muang Pok (Saen Hai sub-district), and Ban Mae Haad (Mueang Haeng sub-district) in Wiang Haeng district, Chiang Mai province of Thailand. These areas are home to ethnic communities that primarily cultivate highland terrace rice and upland rice for domestic consumption. However, the increasing use of chemical herbicides, insecticides, and fertilizers has led to higher production costs and negative environmental impacts, affecting both the surrounding ecosystems and highland communities. The research aimed to enhance rice yields and ensure sufficient production to meet community needs by improving learning processes and introducing appropriate technologies for highland farmers. Thirteen farmers, including community leaders and proactive representatives with a strong interest in agricultural improvement, participated in the study. The following key steps were undertaken to equip participants with the knowledge, skills, and critical thinking required to lead and advance highland rice farming in their communities: 1) Conducting community gatherings in each sub-district, 2) Identifying challenges, proposing solutions, and defining development goals, 3) Sharing technical knowledge on rice cultivation from the Department of Rice, 4) Establishing demonstration plots to showcase and adapt highland rice production technologies, and 5) Assessing the adoption of these technologies by engaging farmers in hands-on activities and monitoring implementation progress. The research introduced both upland rice and highland terrace rice farming technologies, which included optimized seed rate usage, improved plot management, fertilizer application based on soil analysis, pest and disease control, and harvesting at the optimal time. Results showed significant improvements: upland rice yields increased by 5.4% while production costs decreased by 12.6%, and highland terrace rice yields increased by 10.0% with a 10.5% reduction in production costs across 13 demonstration plots. Throughout the process, representative farmers acted as technology disseminators, transferring knowledge to their communities and enabling farmers to collectively address production challenges. This collaborative approach enhanced understanding of rice cultivation practices, improved food security at both household and community levels, and contributed to the sustainable development of highland agriculture.